Methionine Restriction Differentially Modulates Expression of Genes in the Base Excision Repair Pathway in Rat Brain and Liver - Ricardo Gredilla; Monica Lopez-Torres; Ines Sanchez-Roman (Biomolecules)
Methionine restriction (MetR) is a dietary intervention that extends mean and maximum life span in rodents, at least in part, by reducing oxidative stress and promoting DNA stability in different tissues. Regarding DNA stability, DNA repair pathways play a critical role, both in the nuclear and mitochondrial fractions. Base excision repair (BER) is the main one involved in the repair of oxidative damage, as well as the main one in mitochondria. Despite the relevance of DNA repair in DNA maintenance, it is not known whether MetR regulates BER as a mechanism of preserving genomic stability. In this study we analyzed, for the first time, the effect of 40% MetR for 7 weeks on BER in rat brain cortex and liver, focusing on the expression of several key BER genes. In the brain cortex, MetR significantly increased the gene expression of the DNA glycosylase Ogg1 and the DNA endonuclease Ape1 while reducing DNA polymerase γ gene expression. Conversely, MetR led to a general reduction in the expression of BER genes in the liver. Our findings highlight a tissue-specific regulation of the BER gene expression in response to MetR. Different potential mechanisms underlying these changes in BER, such as DNA methylation or activation of signaling pathways, are discussed.